2020
DOI: 10.1007/s40295-020-00224-1
|View full text |Cite
|
Sign up to set email alerts
|

Sensor Configuration Trade Study for Navigation in Near Rectilinear Halo Orbits

Abstract: Deep Space Gateway is a NASA program planned to support deep space human exploration and prove new technologies needed to achieve it. One Gateway requirement is the ability to operate in the absence of communications with the Deep Space Network (DSN) for a period of at least three weeks. In this paper, three types of onboard sensors (a camera for optical navigation, a GPS receiver, and X-ray navigation) are considered to enhance its autonomy and reduce the reliance on DSN. A trade study is conducted to explore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Simulations of hybrid strategies (implementing autonomous navigation methods but still relying on DSN) have shown, as a first remarkable result, the possibility of reducing the workload of DSN and ground operations in general, such as data processing and subsequent satellite uplink. In their work, Yun et al [7] have shown how the combined use of optical navigation, antennas for GPS, and X-ray pulsar navigation could reduce the dependency on DSN to one hour per pass, a six-fold reduction from the nominal DSN-only approach.…”
Section: First Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Simulations of hybrid strategies (implementing autonomous navigation methods but still relying on DSN) have shown, as a first remarkable result, the possibility of reducing the workload of DSN and ground operations in general, such as data processing and subsequent satellite uplink. In their work, Yun et al [7] have shown how the combined use of optical navigation, antennas for GPS, and X-ray pulsar navigation could reduce the dependency on DSN to one hour per pass, a six-fold reduction from the nominal DSN-only approach.…”
Section: First Resultsmentioning
confidence: 99%
“…This so-called co-estimation problem was first solved using cross-linked range measurements within the Linked Autonomous Interplanetary Satellite Orbit Navigation (LiAISON) method [4]. Then, newer works expanded LiAISON results to optical measurements [5], and different sensors have been considered within the concept of data fusion [3,6,7,8]. Among them, X-ray pulsar navigation and, most importantly, cameras for optical navigation have been considered to get measurements from observations of asteroids, other satellites, Moon centers, and landmarks.…”
Section: Current Trends For Navigationmentioning
confidence: 99%
“…All simulations initialize the OCBE with a random initial error and fixed uncertainty dictated by Earth-radar observing in order to approximate SSA hand-off from Earth-based resources to an optical observer. To be approximately consistent with previous navigation studies the 3-sigma position uncertainty is 10 km and the 3-sigma velocity uncertainty is 10 cm/s [18,19]. With the filter selected and initialization specified, modifications to the ballistic OCBE are now presented to aid state estimation in the CR3BP.…”
Section: State Estimationmentioning
confidence: 96%
“…First, scheduling DSN time is difficult because it is already heavily subscribed. Alleviating DSN resources has become important enough that it has resulted in various onboard autonomous navigation studies for vehicles planning to use the network [1,19]. Second, the DSN is not optimized for non-cooperative vehicles and therefore cannot provide the same level of accuracy in those cases.…”
Section: Introductionmentioning
confidence: 99%
“…This so-called co-estimation problem was first solved using cross-linked range measurements within the Linked Autonomous Interplanetary Satellite Orbit Navigation (LiAISON) method [4]. Then, newer works expanded LiAISON results to optical measurements [5], and different sensors have been considered within the concept of data fusion [3,6,7,8]. Among them, X-ray pulsar navigation and, most importantly, cameras for optical navigation have been considered to get measurements from observations of asteroids, other satellites, Moon centers, and landmarks.…”
Section: Current Trends For Navigationmentioning
confidence: 99%